SUHU PENYIMPANAN KREATININ DAN ASAM URAT DALAM AIR KEMIH SELAMA 24 JAM - AAN. Subawa; Sianny Herawati; I Nyoman Wande; I Wayan Putu Sutirta Yasa; Tjokorda Gede Oka (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Creatinine and uric acid is a product that excreted in the urine by normal kidney functions. The examination of creatinine and uricacid in urine is done on 24-hour urine collection. During the storage of the urine, it is recommended to be stored in a refrigerator withthe grade temperatures ranging from 2–8°C and is not recommended to use any preservative for the examination of creatinine anduric acid in urine. To know the comparation of creatinine and uric acid concentrations in urine between the urine tested immediatelyafter the collection with urine that was stored at a temperature 2–8°C and those at room temperature for 24 hours. A total of 45 urinesamples from outpatient clinic that came to the laboratory, were collected in particular urine vacutainer. Each urine sample is divided intothree tubes. The first tube (P1) examined concentrations of creatinine and uric acid immediately after collection, was considered as thebaseline value. The second tube (P2) stored at 2–8°C and the third tube (P3) is stored at room temperature for 24 hours, then followedby the examination of creatinine and uric acid concentrations. The examination of creatinine in urine was using reagent CREP2 RocheDiagnostic and uric acid in urine was using reagent UA2 Roche diagnostics by Cobas Integra ® 400 plus ® instrument. The mean ofcreatinine in urine concentrations which immediately examined (P1) is (125.10±74.85 mg/dL), concentrations after storage at 2−8°C(P2) and at room temperature (P3) were (123.42±73.80 mg/dL) and (124.09±73.95 mg/dL) respectively. Based on the analysis ofone-way ANOVA, there were no significant differences between the concentrations of creatinine in urine immediately checked which werestored at 2–8°C and at room temperature (P>0.05). The mean of uric acid in urine concentrations which immediately examined (P1) is(52.61±35.48 mg/dL), where as after storage at 2–8°C (P2) and room temperature (P3) were (45.11±31.62 mg/dL) and (46.38±28.91mg/dL) respectively. Based on the analysis of one-way ANOVA, there were no significant differences between the concentrations of uricacid in urine immediately checked by those stored at 2–8°C and at room temperature (P>0.05). Based on this study, it can be concludedthat there were no effect of storage temperature on the concentrations of creatinine and uric acid in urine within 24 hours.